Structural and Semantic Organization of the Accentuation Category in Russian and Chinese Political Discourse - Nannan, Zhao (Journal of the Belarusian State University. Philology, 2019)
The article demonstrates structural and semantic organization patterns of the accentuation category in Russian and Chinese political discourse. Speeches of Russian and Chinese political leaders constituted the material for the research. The analysis is carried out with the help of descriptive methods, contrastive-comparative analysis, statistical method. It has been established that the accentuation categories in Russian and Chinese political discourse are formed by five micro-fields: evaluation, emphasis, attention activation, specifications and categoricity/non-categoricity. Each micro-field has a special structure formed by a specific set of core and peripheral accentuators. Certain patterns are revealed at distributing accentuating linguistic units according to the named micro-fields. Thus, evaluation is more common for the lexical level, and addressee’s attention activation is predominantly realized at the syntactic level. Adjectives are used more for evaluation, adverbs are more common for emphasis. Conjunctions are widely used for specifications, and particles are typical for categoricity explication. Micro-fields of the accentuation category do not exist in isolation: they intercommunicate, complement each other and emphasize each other. It is demonstrated by the existence of accentuators performing several functions from several micro-fields simultaneously. The contrastive analysis resulted in the conclusion about the similarity of structural and semantic structures of accentuation fields in discourses in the russian and the chinese languages. Differences concern statistic patterns and involve the frequency of usage of accentuators (for example, usage of conjunctions, adverbs and particles is more typical for texts in the russian language, and accentuating metacommunicative constructions predominate in Chinese speeches).